Menumbuhkan Jiwa Sosial Mahasiswa FAI UMS melalui Pengabdian Kepada Masyarakat di Desa Kleco, Boyolali, Jawa Tengah - Fauzi, Ahmad Akbar; Fitriyan, Yassir Hafidh; Rifky, Mohammad; Mustofa, Triono Ali; Anshori, Ari; Chusniatun (Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service is an implementation of the Tri Dharma of Higher Education aimed at enhancing students’ social awareness and sensitivity toward their surroundings. Conducted by students of the Faculty of Islamic Studies (FAI) at Universitas Muhammadiyah Surakarta through direct engagement with local communities, this program applies a participatory approach involving four stages: observation, planning, implementation, and evaluation–reflection. The results show that student participation effectively fosters social consciousness by strengthening empathy, concern, and social responsibility. Moreover, the program reinforces relationships between students and the community across the fields of education, economics, and health while internalizing Islamic values that help shape moral, empathetic, and integrity-driven character.